The Rise of Virulence and Antibiotic Resistance in &Lt;i>Staphylococcus Aureus</I&gt; 2017
DOI: 10.5772/65960
|View full text |Cite
|
Sign up to set email alerts
|

SOS Response and Staphylococcus aureus: Implications for Drug Development

Abstract: Damage in genetic material is induced through the action of several drugs (directly or indirectly). Specially, antimicrobials from quinolone class (such as ciproloxacin) induce DNA damage that promotes the formation of the RecA ilament leading to auto-cleavage of LexA and allows the expression of SOS genes, including the error-prone polymerase (like umuC). The SOS pathway plays a critical role in the acquisition of mutations that lead to the emergence of antibiotic-resistant bacteria and the spread of virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Expression of such proteins is induced by H 2 O 2 stress 31 . SOS response proteins UvrA and UvrC, and bleomycin resistance protein had also increased significantly in the presence of NW-850-5, which mediate repair of DNA damage 32,33 , along with histone-like DNA-binding protein HU, which is involved in DNA stabilisation under extreme environmental conditions 34 . In addition to oxidative stress, another key theme of S. aureus DEPs was protein expression.…”
Section: Characterisation Of Tio 2 Nanopillars On Titanium Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Expression of such proteins is induced by H 2 O 2 stress 31 . SOS response proteins UvrA and UvrC, and bleomycin resistance protein had also increased significantly in the presence of NW-850-5, which mediate repair of DNA damage 32,33 , along with histone-like DNA-binding protein HU, which is involved in DNA stabilisation under extreme environmental conditions 34 . In addition to oxidative stress, another key theme of S. aureus DEPs was protein expression.…”
Section: Characterisation Of Tio 2 Nanopillars On Titanium Substratementioning
confidence: 99%
“…10a). Given that ROS mediate damage of DNA, lipids and proteins 32,39 , the increased quantity of H 2 O 2 could be expected to induce changes in bacterial envelope morphology. Following 24-h incubation, the density and coverage of S. aureus and E. coli were notably higher on control compared to NW-850-5 discs ( Fig.…”
Section: Characterisation Of Tio 2 Nanopillars On Titanium Substratementioning
confidence: 99%
“…As biofilm emerges as a stress response to hostile environment, different SOS systems are triggered in the presence of stressful conditions, such as antibiotic treatments, starvation, or oxidative stress, to repair damaged DNA caused by these threats [ 79 ]. Starvation and the associated SOS response can mediate biofilm-specific tolerance to antibiotic such as ofloxacine, and it was also shown that subinhibitory concentrations of quinolones can induce an SOS response and elevate the mutation rate [ 80 , 81 ].…”
Section: Antibiotic Failure In Pji Due To S Aureus mentioning
confidence: 99%
“…Generated by the host, reactive oxygen species are also linked with antibiotic tolerance during systemic S. aureus infections [ 82 ]. The SOS response also affects the expression of virulence factors, mutagenesis, and the frequency of SCVs [ 79 , 83 ]. This phenotype switch in S. aureus is described as a consequence of drug treatments, reactive oxygen species, low pH, and starvation, and is also linked to the internalization ability [ 12 , 36 ].…”
Section: Antibiotic Failure In Pji Due To S Aureus mentioning
confidence: 99%